The Effect of Using the Daily Undulating Periodization (DUP) Model on Increasing Muscle Endurance - Taupiqkurrohman, Miqdad; Subarjah, Herman; Imanudin, Iman (Yayasan Insan Mulia Bima, 2024)
This study aims to examine the effect of using the daily undulating periodization (dup) model on increasing muscle endurance. The results showed that using the Daily Undulating Periodization (DUP) model can significantly improve muscular endurance compared to the linear or traditional periodization model. The method used in this research is one group pre test - post test design. The participants in this study were 15 undergraduate students of Universitas Pendidikan Indonesia. The research was conducted for 8 weeks and treatment was carried out 3 times a week in 24 sessions, which were held at the FPOK Fitness Laboratory. The data were then analyzed using normality and homogeneity tests and paired sample t-test. From the results of the data processing above, it shows that the normality test results for the Upperbody pre test (0.326) > 0.05 and for the Upperbody post test (0.377) > 0.05, for the Lowerbody pretest (0.357) > 0.05 and for the Lowerbody post test (0.696) > 0.05, it can be concluded that the data obtained is normally distributed. Based on the data above, the results of the homogeneity of Push Up p = 0.935 and the Wall Sit variable = 0.652, which means that the data is homogeneous. Based on the table above, the Push Up and Wall Sit experimental groups that have received treatment have a significant value of 0.000 <0.05, so H0 is rejected. So it can be concluded that there is an effect of using the daily undulating periodization (DUP) model on increasing muscle endurance.